2014
DOI: 10.1016/j.iref.2013.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The global financial crisis: World market or regional contagion effects?

Abstract: In the last two decades, the world economy has been challenged by different economic and financial crisis. These events have captured researchers' attention, and in particular the analysis of contagion effects derived from stock market shocks have been a focal point of interesting discussions. However, there is little consensus on how contagion should be defined and indentified. Consequently, this paper contributes to the already settled debate on the area proposing the analysis of contagion effects in a world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…10 Boyer, Gibson, and Loretan (1999) and Loretan and English (2000) made the same point and derive similar bias correction methods independently. Recent work by Morales and Andreosso-O'Callaghan (2014) also provided similarly weak evidence of contagion in the international stock market. 11 Bekaert, Harvey, and Ng (2005) also point out that Forbes and Rigobon's method is not valid in the presence of common shocks.…”
Section: Literature Reviewmentioning
confidence: 95%
“…10 Boyer, Gibson, and Loretan (1999) and Loretan and English (2000) made the same point and derive similar bias correction methods independently. Recent work by Morales and Andreosso-O'Callaghan (2014) also provided similarly weak evidence of contagion in the international stock market. 11 Bekaert, Harvey, and Ng (2005) also point out that Forbes and Rigobon's method is not valid in the presence of common shocks.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Lucey and Voronkova (2008) found that in the long run the Russian equity market remained isolated from the influence of several developed international markets as well as the equity markets of Hungary, the Czech Republic and Poland, before and after the 1998 crisis. Morales and Andreosso-O'Callaghan (2014), in their comprehensive study of 58 countries, documented that there are no significant contagion effects derived from the U.S. stock markets, either at world level and or at a regional level. Moreover, their results suggested that there was a spillover effect of the U.S. sub-prime crisis on selected markets rather than contagion to most of the countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…economies have overlooked the importance of other emerging economies, specifically the countries that were selected for this study (i.e., Malaysia, South Korea and Pakistan). Furthermore, numerous studies have focused only on pre-crisis and crisis time periods (e.g., Chakrabarti andRoll, 2002 andMorales &Andreosso-O'Callaghan, 2014). The spillover effect has not, however, been measured after the financial crisis period, to check whether the emerging stock markets adjust to normal conditions or not.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Especially since the collapse and bankruptcy of Lehman Brothers on September 2008, credit flows dried up, lender confidence dropped with investors repatriating funds to domestic markets and world economies dipped into recession because of international and domestic aggregate demand plummeted (Milesi-Ferreti and Tille, 2011;Morales and Andreosso-O'Callaghan, 2014), Regardless of policy action, especially in the US, had treated to contain the symptoms of the financial turmoil, the crisis spillovered from . At the beginning of the financial crisis however the focus was on the actions of Central banks to address the financial shock and expansionary measures to reactivate the economies, while there was little concern about public debts.…”
Section: Introductionmentioning
confidence: 99%
“…1 Economic literature on different topics of the financial crisis and debt crisis is vast. Among other topics we can find the accumulation of macroeconomic, fiscal and financial vulnerabilities prior to the financial crisis itself (Wyplosz, 2006;Caruana and Avdkiev, 2012), aspects related to what happened in different asset markets (Dwyer and Tkac, 2009;Melvin and Taylor 2009, among others), policy studies, transmission of shocks and asset pricing (Baba and Packer, 2009;Dimitriou et al, 2013;Morales and Andreosso-O'Callaghan, 2014), the European debt crisis (Lane, 2012;Mody andSandri, 2012, De Grawve, 2010). On the other side, econophysics literature has analyzed different aspects such as; the structure and resilience of financial networks affected by extreme event (Kantar et al, 2012;Preis et al 2012;Peron et al 2012), the network structure and systemic risks (Anand et al, 2012;Pozzi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%